Incidence of retromolar foramen in human mandibles: ethnic and clinical aspects - Rossi, Ana Claudia; Freire, Alexandre Rodrigues; Prado, Guilherme Bevilacqua; Prado, Felippe Bevilacqua; Botacin, Paulo Roberto [UNESP]; Ferreira Caria, Paulo Henrique (Soc Chilena Anatomia, 2012)
The retromolar foramen allows the passage of the neurovascular bundles that contribute to nutrition and innervation of the pulp and periodontium of the lower teeth. Knowledge of this anatomical variation may prevent complications in the anesthesia and surgical procedures in this area and serve as an anatomical landmark for ethnic identification. The aim of this study was to evaluate the impact of the retromolar foramen in human mandibles of adult Brazilians and discuss the clinical and ethnic related to the presence of this foramen. Were evaluated 222 human mandibles, dry, adults, Brazilians, independent of gender. The evaluation was performed by two examiners who standardized search from a previous anatomical study. The mandibles were analyzed: the presence of the retromolar foramen (bilateral or unilateral), the presence of the foramen on right and left sides, and the number of foramens present on each side. It was found that 59 had at least one mandible retromolar foramens resulting in an incidence of 26.58%. The retromolar foramen was present unilaterally in 41 mandibles and 18 bilaterally, with incidences of 18.47% and 12.16% respectively. on the right side, the retromolar foramen was present in incidences of 16.22% and 18.92% respectively The analysis of the right side of the mandibles revealed that 47.46%, 21.21% and 3.03% had one, two and three foramens, respectively The left side showed 55.93%, 16.22% and 8.11% of the 222 mandibles with one, two and three retromolar foramens, respectively The incidence of retromolar foramen in the Brazilian population is significant and should be considered in the planning and execution of procedures in several areas of clinical practice dentistry in order to avoid complications. Moreover, it was found that the incidence of retromolar foramen contributes to differentiation of ethnic groups in the area of forensic anthropology.

El foramen retromolar permite el paso de los haces neurovasculares que contribuyen a la nutrición y inervación de la pulpa y periodonto de los dientes mandibulares. Conocer sus variaciones anatómicas pueden prevenir complicaciones de la anestesia y procedimientos quirúrgicos, y servir de punto de referencia anatómico para la identificación étnica. El objetivo de este estudio fue evaluar el impacto del foramen retromolar en mandíbulas humanas de brasileños adultos y discutir la relación clínica y étnica de la presencia de este foramen. Se evaluaron 222 mandíbulas humanas secas de adultos brasileños, independiente del sexo. La evaluación fue efectuada por dos examinadores que realizaron búsquedas estándar de un estudio anatómico anterior. En las mandíbulas se examinaron: la presencia del foramen retromolar (bilateral o unilateral), lados (derecho e izquierdo), y el número de forámenes presentes en cada lado. En 59 mandíbulas se observó al menos un foramen retromolar, una incidencia del 26,58%. El foramen retromolar estuvo presente de manera unilateral en 41 mandíbulas, bilateralmente en 18, con una incidencia del 18,47% y 12,16%, respectivamente. En el lado derecho, el foramen retromolar estuvo presente en el 16,22% y 18,92% respectivamente. El análisis de la parte derecha de la mandíbula reveló que 47,46%, 21,21% y 3,03% tuvo uno, dos y tres forámenes, respectivamente. El lado izquierdo mostró 55,93%, 16,22% y 8,11% con uno, dos y tres forámenes retromolares, respectivamente. La incidencia del foramen retromolar en la población brasileña es significativo y se debe considerar en la planificación y ejecución de los procedimientos en varias áreas de la odontología clínica con el fin de evitar complicaciones. Por otra parte, se constató que la incidencia del foramen retromolar contribuye a la diferenciación de los grupos étnicos en el área de la antropología forense.
Incidencia del foramen retromolar en mandibulas humanas: aspectos étnicos y clínicos
Keywords: Foramen; Retromolar; Anesthesia; Mandible